Evaluasi Manajemen Tata Ruang Wisata Dan Ruang Terbuka untuk Meningkatkan Kunjungan Wisata Dan Pad Kota Palembang - Dimitri Yulianti; Herlan Junaidi (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Palembang city is one of the cities that has a very good tourism attraction. This city has tourist destinations, cultural heritage, and culinary tourism. As a leading tourism city, Palembang City should be able to manage tourism spatial planning and open space for optimizing Palembang City tourist visits. This is because the city of Palembang has great tourism potential because it is supported by the ownership of tourism objects, culinary tourism, and open spaces that can be used for various purposes.This study aims to evaluate the management of the utilization of Tourism Spatial Planning and Open Space by the Palembang City Government and to find out the factors that support and hinder the optimization of tourist visits that have an impact on the local revenue of Palembang City. The stages start from initial observation, data collection, data analysis, and conclusions. The rationale for this research is the case study method with the type of mix method. Data collection techniques using semi-structured interviews, selecting informants using expert analysis. Observations were made open. Test the validity of the data using triangulation and member checking. Data analysis techniques used in this research are Geographic Information System (GIS), Arc Map, Logic Model, and Thematic Analysis. The results of this study indicate that the spatial arrangement of tourism and open space has the potential to increase tourist visits and PAD in Palembang City. Supporting factors for tourist visits are human resources and budget. The inhibiting factor is the pandemic and the availability of spatial data. Keywords : Thematic analysis, logic model, tourism, GIS